2017
DOI: 10.1007/s10068-017-0290-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical properties and probiotic survivability of symbiotic oat-based beverage

Abstract: The objectives of this study were to develop a symbiotic oat-based beverage (SOB) and to analyze its physiochemical properties and the probiotic survivability. The beverage base was prepared by fermenting a mix containing oat flour (10%, w/w), sugar (4%, w/w), and inulin (1%, w/w) with a commercial (0.003%, w/w) at 30 °C for 12 h. The SOB was formulated using the fermented oat base, sugar, stabilizers (pectin and λ-carrageenan), vitamin C, and citric acid. The beverage was analyzed for total solids (11.65 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
5
17
0
Order By: Relevance
“…L. plantarum reached populations of approximately 9 Log CFU/mL after 4 h of fermentation at 30 °C ( Table 2 ). These results confirm that oat substrate has nutrient content high enough to support the growth and metabolism of lactic acid bacteria, as earlier reported by other researchers [ 14 , 16 , 17 ]. Similar starter bacteria population was observed in a quinoa beverage obtained by fermentation with L. plantarum 0823, L. casei Q11 and L. lactis ARH74 (1% v / v of each strain) for 6 h at 30 °C [ 34 ], while lower viable counts were reported in oat after fermentation with L. plantarum NCIMB 8826, L. acidophilus NCIMB 8821 or L. reuteri NCIMB 11951 (1% v / v ) for 4–8 h at 30 °C [ 16 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…L. plantarum reached populations of approximately 9 Log CFU/mL after 4 h of fermentation at 30 °C ( Table 2 ). These results confirm that oat substrate has nutrient content high enough to support the growth and metabolism of lactic acid bacteria, as earlier reported by other researchers [ 14 , 16 , 17 ]. Similar starter bacteria population was observed in a quinoa beverage obtained by fermentation with L. plantarum 0823, L. casei Q11 and L. lactis ARH74 (1% v / v of each strain) for 6 h at 30 °C [ 34 ], while lower viable counts were reported in oat after fermentation with L. plantarum NCIMB 8826, L. acidophilus NCIMB 8821 or L. reuteri NCIMB 11951 (1% v / v ) for 4–8 h at 30 °C [ 16 ].…”
Section: Resultssupporting
confidence: 91%
“…Recent studies have demonstrated that germination efficiently increased soluble phenolic content in cereals [ 18 , 19 , 20 ]. The bio-conversion of phenolic conjugated forms to the corresponding aglycones and release of bound forms to the corresponding free forms during lactic acid fermentation has been also well established [ 17 , 53 ]. Taking together, all these findings suggest that fermentation of sprouted oat is a promising approach to manufacture novel antioxidant cereals-derived foods enriched in bioaccesible phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown that fermented oat beverages may be potential probiotic carriers. They resulted in optimization of the fermentation process and the beverage formulations, reaching high microbial levels (˃10 7 CFU/mL) during production and storage, and were able to maintain the β-glucan content at the end of storage [ 41 , 42 , 43 , 44 , 45 ]. The viability and in vitro probiotic potential were recently investigated by Funck et al [ 46 ] in oat beverages fermented with L. curvatus P99.…”
Section: Non-dairy Fermented Beverages As Vehicles For Bioactive Cmentioning
confidence: 99%
“…Therefore, the use of LAB‐derived EPS in the development of functional polysaccharide products with health benefits is worthy of investigation. Moreover, yacon extract, inulin and oat are currently used as prebiotics combined with probiotic LAB to develop symbiotic products …”
Section: Introductionmentioning
confidence: 99%